Does Early Chemotherapy Improve Survival in Advanced Endometrial Cancer?. (November 2019) - Boothe, Dustin; Orton, Andrew; Kim, Jaewhan; Poppe, Matthew M.; Werner, Theresa L.; Gaffney, David K.
Abstract : Objectives: In endometrial cancer, the appropriate sequence of adjuvant chemotherapy (aCT) and adjuvant radiation therapy (aRT) is unclear. We aim evaluated whether early chemotherapy is associated with improved overall survival (OS) and cancer-specific survival (CSS). Methods: Endometrial cancer patients that received aCT and aRT were selected from the SEER-Medicare database. Early chemotherapy was defined as receiving aCT before aRT, with or without additional aCT ("sandwich" regimens). All other patients received a full course of aRT before chemotherapy with or without concurrent chemotherapy. Univariate and multivariate Cox proportional hazards regression was utilized to assess the impact of clinical and demographic factors on OS. Results: We selected 597 patients for analysis. Median age and was 72 years; 85% of patients were white. Overall, 68% of women had FIGO (International Federation of Gynecology and Obstetrics) stage III disease and 77% received 4 to 6 cycles of chemotherapy. Five-year OS (66.6% vs. 62.4%, P =0.46) and 5-year CSS (71.1% vs. 71.2%, P =0.88) was not significantly improved among those receiving early chemotherapy. In addition, early chemotherapy did not improve OS (hazard ratio [HR]=0.87; 95% confidence interval [CI]: 0.56-1.34, P =0.53) or CSS (HR=1.21; 95% CI: 0.82-1.79, P =0.34) on multivariate analysis. Compared with 1 to 3 cycles, receiving 4 to 6 (HR=0.48, 95% CI: 0.26-0.87, P =0.02), and ≥7 cycles (HR=0.42, 95% CI: 0.20-0.89, P =0.02) of chemotherapy was associated with improved OS. Conclusion: No differences in OS or CSS were noted among endometrial patients receiving early chemotherapy. However, the number of chemotherapy cycles was associated with prolonged survival.